Social media use and hypertension knowledge among undergraduate students during the COVID-19 pandemic in Faculty of Medicine and Health Sciences, Universiti Putra Malaysia - Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Xuan, Low Zhi; Selvanesan, Kasendra; Noorazalan, Akmal Aiman (Universiti putra Malaysia, 2022)
Introduction: : Malaysian hypertension prevalence is high at 30% and is the highest risk factor for mortality. Good hypertension knowledge suggests a favourable outcome. Online sources are a popular method of obtaining information especially in young adults and during the pandemic. Our objective is to determine health information seeking online, use of social media, and hypertension knowledge among undergraduate students. Methods: This is a cross-sectional study conducted in the Faculty of Medicine and Health Sciences (FHMS), Universiti Putra Malaysia (UPM). Random sampling was done. An online questionnaire with four sections: (1) socio-demographic data; (2) use of social media; (3) health information sought online; and (4) hypertension knowledge was used . Data were analysed using the SPSS version 25 using Independent T tests and one-way ANOVA to identify factors associated with hypertension knowledge. Results: Mean (SD) age of 286 respondents was 21(1.2) years. Most respondents were female, 207(73.1%), Malays, 177(61.9%) and taking the Medicine course 127(44.4) with a mean of 9.50(4.50) hours of internet usage daily. Many respondents 196(68.5%) looked for information on hypertension online. The mean score for hypertension knowledge was 8.32(1.46); classified as good knowledge. Hypertension knowledge was significantly associated with race (p<0.001), type of course (p<0.001), year of study (p<0.001) and type of health information searched online (p=0.010). Conclusion: We found significant better knowledge in Indians compared to Malays, medical students compared to biomedical sciences and occupational health, students in year 5 compared to years 1&2. Participants that searched on hypertension online had better knowledge on hypertension.